Diminished Expression of Galectin-3 Around Blisters in Bullous Pemphigoid: An Immunohistochemistry Study - Aghighi, Maryam; Smoller, Bruce (Dermatology Practical & Conceptual, 2020)
Background: Bullous pemphigoid (BP) is a subepidermal blistering disorder caused by autoantibodies directed against hemidesmosomal proteins. Many patients with BP demonstrate circulating IgE autoantibodies. Although the role of IgE in the pathogenesis of BP is unknown, a correlation between IgE antibodies and eosinophilia has been observed. Soluble CD23 and galectin-3 are the main elements of the IgE group. The roles for CD23 in BP as a potential biomarker and IgE production regulator have been characterized, but no studies have evaluated any roles for galectin-3 in this disease.Objectives: In this study, we evaluated galectin-3 expression in BP as a first step in assessing its role in the pathogenesis of this autoimmune blistering process. Patients and Methods: Sixty specimens diagnosed as BP were stained with antibodies to galectin-3. The percentages of nuclear and cytoplasmic galectin-3 expression and staining intensity were evaluated.Results: There was a significant difference in galectin-3 cytoplasmic and nuclear expression within keratinocytes immediately surrounding and above the blisters: (1) cytoplasmic (mean = 17.2% ± 2.4%) vs adjacent unaffected skin (mean = 66.7% ± 2.0%, P < 0.0001) and (2) nuclear (mean = 1.9% ± 0.4%) vs adjacent unaffected skin (mean = 13.2% ± 1.2%, P < 0.0001).Conclusions: Lower expression of galectin-3 around blisters in BP may suggest a role as an adhesion molecule. Loss of galectin-3 may add to the extension of blister formation by initiating cell-extracellular matrix disassembly and may be involved with the associated dermal inflammation and the eosinophil chemotaxis. Further studies will be necessary to elucidate the result of this observed loss on disease pathogenesis.